2020
DOI: 10.1002/jpen.1988
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Inflammatory Bowel Disease Patients Requiring Long‐Term Parenteral Support in the Present Era of Highly Effective Biologic Therapy

Abstract: Background Despite advances in the medical management of inflammatory bowel disease (IBD), a subset of patients may require extensive surgery, leading to short‐bowel syndrome/intestinal failure requiring long‐term home parenteral nutrition (PN) or customized intravenous fluid (IVF) support. Our aim was to further define the characteristics of IBD patients requiring home PN/IVF. Methods This is an observational study from a prospective IBD research registry. Patients receiving long‐term home PN/IVF support duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…A large percentage of our patient cohort had documented tobacco use. Smoking has been associated with IF in inflammatory bowel disease 13 ; our study offers further support to the notion that smoking may be a risk factor for development of severe malnutrition requiring PS in patients with SBS.…”
Section: Discussionsupporting
confidence: 82%
“…A large percentage of our patient cohort had documented tobacco use. Smoking has been associated with IF in inflammatory bowel disease 13 ; our study offers further support to the notion that smoking may be a risk factor for development of severe malnutrition requiring PS in patients with SBS.…”
Section: Discussionsupporting
confidence: 82%
“…The reason for not trialling biologics was unclear, but we postulate that a perceived futility and concern for infective complications in the setting of intestinal stulae or impending surgeries may have impacted clinicians' and/or patients' willingness to initiate a new therapy, especially when biologics were still novel. Only a few studies have reported on the use of biologics in CDIF patients before the onset of IF, with wide-ranging rates from 4% to 80%, 10,37 and one study found non-use of anti-TNF was associated with developing IF. 18 Limited e cacy of biologics in preventing surgery has been found in CDIF patients after IF onset.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal failure (IF), de ned as the reduction of gut function below the minimum necessary for the absorption of macronutrients and/or water and electrolytes, 1 is a rare but severe end-organ sequelae of Crohn's disease (CD). [2][3][4] While IF affects at most 80 people per million, 5 30-46% of IF is caused by CD, [6][7][8][9][10][11][12] and signi cant resources and expertise are required to manage IF patients with home parenteral support (HPS). [13][14][15] Previous studies reported long-term cumulative incidences of IF from CD from 3.4-18.4%, [16][17][18] indicating a non-negligible risk.…”
Section: Introductionmentioning
confidence: 99%
“…They described that HPN use was significantly associated with smoking, narcotic use, IBD-related surgeries, and lower quality-of-life scores. They found that these refractory patients had a 15-fold increase in annual median health care charges compared to control IBD patients[ 28 ].…”
Section: Sbs-if In Crohn’s Diseasementioning
confidence: 99%